Social and emotional education with Australian Year 7 and 8 middle school students: A pilot study. (April 2017) - Midford, Richard; Cahill, Helen; Geng, Gretchen; Leckning, Bernard; Robinson, Gary; Te Ava, Aue
Objective: This pilot study sought to better understand what can be achieved by an evidence-based classroom social and emotional education programme. Design and Methods: A 10-lesson, classroom-based programme that taught about emotional literacy, personal strengths, coping and problem-solving strategies, stress management, emotional regulation and support seeking was provided to 56 students in Years 7 (13 years) and 8 (14 years) in an Australian middle school. Teachers were trained to deliver the programme, with participatory modelling of each activity. Before and after delivery of the programme, students were surveyed for their social and emotional wellbeing using the Kessler 10 (K10) instrument for non-specific psychological distress; the 'Internal Assets', 'School Resources' and 'Cooperation and Communication' questions from the Resilience and Youth Development Module (RYDM) of the California Healthy Kids Survey (CHKS); and questions developed for this study on class connectedness and social and emotional skills. Subsequent to programme completion, focus groups were conducted with teachers and participating students to gauge programme fidelity, utility and engagement. Results: There was an improvement in psychological distress that approached significance ( t  = 2, df = 42, p  = .053), although the symptomatic score remained in the range indicative of medium-level distress. Cooperation and communication improved significantly ( t  = −2.34, df = 42, p  = .024) as did class connectedness ( t  = −2.46, df = 43, p  = .018). There was no change in individual resilience factors, school protective factors, or social and emotional skills. The focus groups were generally positive about the programme, but indicated fidelity was compromised, mainly because the lesson periods were too short. Conclusion: While this small-scale pilot study has a number of limitations, it does indicate the need to improve the psychological wellbeing of middle school students. The findings also provide evidence that brief social and emotional education programmes can have some positive effects.